Pengaruh Viral Marketing Dan Online Marketing Terhadap Keputusan Pembelian Dengan Kepercayaan Konsumen Sebagai Variabel Intervening (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2016 Pembeli Accessories Gadged Di Tokopedia) - Selvia Sulaksana Andi Putri; N. Rachma; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study was conducted to determine the effect of viral marketing and online marketing on purchasing decisions with consumer confidence as an intervening variable in FEB UNISMA 2016 class of shadded accessories buyers at Tokopedia. Which is located at Jl. MT. Haryono No.193, Dinoyo, Kec. Lowokwaru, Malang City, East Java 65144. The method used is explanatory research that aims to explain the position of each variable and its influence between one variable with another variable, and the source of the data used is primary data by distributing linkert-scale questionnaires to FEB UNISMA students force 2016. The sample calculation in this study uses the malhotra formula which produces 100 respondents. The results of this study are viral marketing variables, online marketing directly affect consumer confidence, viral marketing variables, online marketing directly influence purchasing decisions, consumer confidence variables directly influence purchasing decisions, and viral marketing and online marketing have indirect effects on purchasing decisions with consumer confidence as an intervening variable.Keywords: viral marketing, online marketing, purchasing decisions, consumer confidence.